On low-energy impact response of ultra-high performance concrete (UHPC) panels. (15th February 2016) - Verma, Mohit; Prem, Prabhat Ranjan; Rajasankar, J.; Bharatkumar, B.H.
Abstract: This paper presents the experimental, numerical and analytical investigations carried out to understand the low-energy impact response of ultra-high performance concrete (UHPC) panels for different fiber volume, thickness and impactor energy. Concrete panels of sizes 350 × 350 × 10 mm and 350 × 350 × 15 mm were cast with three different fiber volumes — 0% (R1), 2% (R2) and 2.5% (R3). Two panels with mix R2 and one with mix R1 and R3 were cast for each impactor energy and panel thickness. The impact tests were performed with a 10 mm diameter drop-weight hemispherical impactor of mass 5.41 kg for three energy levels (10, 15 and 20 J). The impact response of UHPC panels was predicted using finite element simulation and spring-mass models. The results obtained from FEM and spring-mass models corroborate well with those obtained from the experiments ( R 2 > 0.8 and mean absolute percentage error (MAPE) <20%). Based on the parametric study carried out to, peak impact load was found to be more sensitive to impactor energy and thickness of the panel than the percentage of fiber volume. In the end, a design flow chart is proposed to arrive at the optimum thickness of the UHPC panel subjected to impact loading. Graphical abstract: Highlights: Experimental evaluation of low-velocity impact response of ultra-high performance concrete (UHPC) panels for different fiber volume, thickness and impactor energy. The increase in the impactor energy causes an increase in the peak impact load. The peak impact force experienced by the panel increases with the thickness of the panel. FEM with SPH particle conversion was found to emulate fragmentation due to impact (R2 < 0:8 and MAPE < 20%). The spring-mass models were also able to predict the impact-force time history of UHPC panels quite reasonably (R2 < 0:9 and MAPE < 10%).